Widespread distribution of ascending fluids transporting mantle helium in the fore-arc region and their upwelling processes: Noble gas and major element composition of deep groundwater in the Kii Peninsula, southwest Japan. (1st June 2016) - Morikawa, Noritoshi; Kazahaya, Kohei; Takahashi, Masaaki; Inamura, Akihiko; Takahashi, Hiroshi A.; Yasuhara, Masaya; Ohwada, Michiko; Sato, Tsutomu; Nakama, Atsuko; Handa, Hiroko; Sumino, Hirochika; Nagao, Keisuke
Abstract: Chemical and isotopic studies including analyses of noble gases were comprehensively conducted on the groundwater of the entire Kii Peninsula, which is located in the fore-arc region of southwest Japan. Groundwater of Na–Cl–HCO3, Na–HCO3 –Cl, and Na–Cl types was shown to be distributed across the whole area. Groundwater in the inland central part of the peninsula shows relatively low salinity, whereas groundwater from the area along the ENE-trending Median Tectonic Line (MTL), on the north side of the peninsula, shows high salinity (up to 18, 800 mg/L of Cl − ) and the presence of unusual heavy oxygen isotopes. This trend is similar to that documented in saline waters from the Arima region (the so-called "Arima-type thermal water"). High 3 He/ 4 He ratios relative to the atmospheric value (up to 6.7 Ra) were recorded throughout the Kii Peninsula, covering a wider area than documented previously. The saline groundwater is also strongly depleted in 20 Ne and heavy noble gases. From the wide distribution of high 3 He/ 4 He values and the associated 20 Ne and Cl − concentrations, we infer that aqueous fluids derived from dehydration of the subducting slab are present at depth beneath almost the entire Kii Peninsula. These aqueous fluids may ascend along the major north-dipping boundary faults. The isotopic composition of groundwater from the southern part of the peninsula suggests that the contribution from these dehydration-derived fluids is relatively small in this region. However, volatile components (e.g., noble gases and CO2 ) in the groundwater of this area may originate from the dehydration-derived fluids. Upwelling of Arima-type thermal water of the Na–Cl–HCO3 type is expected to undergo a phase separation of volatile species due to decompression as the fluid ascends. The variety of water types documented may be due to this water–gas separation and the subsequent incorporation of gaseous species into shallow meteoric groundwater. The observed high 3 He/ 4 He ratios in the absence of a mantle wedge below the southern part of the Kii Peninsula may reflect the oblique ascent of these fluids along north-dipping boundary faults.